Long-term down-regulation of GABA decreases orientation selectivity without affecting direction selectivity in mouse primary visual cortex - Hagihara, Kenta M.; Ohki, Kenichi (Frontiers in Neural Circuits, 2013)
Inhibitory interneurons play important roles in the development of brain functions. In the visual cortex, functional maturation of inhibitory interneurons is essential for ocular dominance plasticity. However, roles of inhibitory interneurons in the development of orientation and direction selectivity, fundamental properties of primary visual cortex, are less understood. We examined orientation and direction selectivity of neurons in GAD67-GFP (Δneo) mice, in which expression of GABA in the brain is decreased in the newborn. We used in vivo two-photon calcium imaging to examine visual response of neurons in these mice and found that long-term decrease of GABA led to increase of response amplitude to non-preferred orientation of visual stimuli, which decreased orientation selectivity. In contrast, direction selectivity was not affected. These results suggest that orientation selectivity is decreased in mice with GABA down-regulation during development.